El peculado en contratación pública durante el estado de emergencia y las consecuencias jurídico-penales recaídas en servidores públicos de Chimborazo - Eduardo Xavier, López Yerovi (2021)
ABSTRACT: This research develops a legal, doctrinal, and case study on the crime of embezzlement in public procurement during the State of emergency. The legal-criminal consequences generated by improper public contracting in a state of emergency were analyzed. The existence of illegal public contracting by state authorities responsible for contracting was identified, and the measures that the State has taken to prevent violation of the regulations. The efficiency of the administration of justice against public servants of Chimborazo, prosecuted and sentenced for embezzlement, was analyzed. Objectives were achieved through descriptive-documentary, qualitative research was developed, with a non- experimental design, since the problem was observed as it occurs in its context. A survey was applied to collect information from administrators of justice in Chimborazo, public servants, and citizens in general. The survey determined that the abuse in emerging public contracting is evident, palpable, and visible, trying to satisfy an indispensable need in times of emergency, omitting several procedures of regular public procurement. It was thus giving way to committing crimes of corruption (embezzlement), which most of the time remain in impunity. By way of conclusion, it should be noted that the administration of justice partially complies with its powers since a different trial is applied to authorities and ordinary public servants who have committed embezzlement crime.